2015
DOI: 10.1021/acs.jpcc.5b01937
|View full text |Cite
|
Sign up to set email alerts
|

Heterodyne-Detected Achiral and Chiral Vibrational Sum Frequency Generation of Proteins at Air/Water Interface

Abstract: We present complex achiral and chiral vibrational sum frequency generation (VSFG) spectra at the air/ water interface of protein solutions by using heterodynedetected VSFG. Bovine serum albumin, pepsin, concanavalin A, and α-chymotrypsin were measured as model proteins. The obtained achiral Im[χ (2) ] spectra gave us insights into the molecular orientation of protein molecules and water at the interface. From the chiral Im[χ (2) ] spectra in the NH stretching and amide I regions, the secondary structures of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 57 publications
2
58
0
Order By: Relevance
“…There have been many developments in measuring phase-resolved spectra of the much narrower spectral features in the C-H stretching vibration region and protein amide band region, etc. [79,[177][178][179][180]. However, as discussed in Section 3.2, when there are non-negligible bulk contributions, such as the (3) χ mechanism from charges surfaces/interfaces, the notion that the imaginary SFG-VS spectrum contains only the absorptive term of the susceptibility can no longer be taken for granted, and the interpretation of the SFG-VS imaginary spectra based only on this notion needs to be cautioned and carefully examined [29], particularly for charged aqueous surfaces/interfaces [92,181] and aqueous surfaces/interfaces of accumulated ions [93,182].…”
Section: Accuracy Of Phase Reference In Phase-resolved Sfg-vsmentioning
confidence: 99%
“…There have been many developments in measuring phase-resolved spectra of the much narrower spectral features in the C-H stretching vibration region and protein amide band region, etc. [79,[177][178][179][180]. However, as discussed in Section 3.2, when there are non-negligible bulk contributions, such as the (3) χ mechanism from charges surfaces/interfaces, the notion that the imaginary SFG-VS spectrum contains only the absorptive term of the susceptibility can no longer be taken for granted, and the interpretation of the SFG-VS imaginary spectra based only on this notion needs to be cautioned and carefully examined [29], particularly for charged aqueous surfaces/interfaces [92,181] and aqueous surfaces/interfaces of accumulated ions [93,182].…”
Section: Accuracy Of Phase Reference In Phase-resolved Sfg-vsmentioning
confidence: 99%
“…SFG-VS, a second-order nonlinear optical technique, is a powerful tool for the identification of interfacial molecular structures and dynamics in situ and in real time. , It has been applied to determine the structures of peptides and proteins at different interfaces by probing amide I vibrations. , Specially, the β-sheet structure is active in the amide I spectra with chiral-sensitive polarization measurements (such as psp and spp), whereas the α-helical or unordered structures are both silent. , SFG-VS is therefore an ideal method to characterize the transition between an α-helix and a β-sheet at the interface . Unfortunately, different β-sheet structural types (including β-hairpin-like monomers, β-sheet oligomers, and fibrils) all contribute to chiral amide I signals.…”
Section: Introductionmentioning
confidence: 99%
“…Because SFG signals rely on a tensor product of the IR transition dipole moment and the Raman polarizability tensor, the amide II SFG signals are too weak to be detected in the disordered, α-helical structure and β-hairpin-like structure. Indeed, with the exception of one example of an amide II signal reported in an intermolecular β-sheet structure by Yan et al, the amide II SFG spectra have not been applied to address the issue of amyloid formation when the SFG technique was applied to investigate the interfacial proteins. , However, some recent studies have shown that upon formation of multistranded β-sheet structures, long-range vibrational coupling from intermolecular β-sheet contacts can largely enhance the amide II signals and make the amide II Raman spectra become visible; see Table S1. For example, the amide II Raman signals are absent in the disordered α-synuclein and appear when α-synuclein starts to aggregate to form oligomeric β-sheet structures. , It can be naturally anticipated that amide II SFG signals are active in β-sheet oligomers and fibrils.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, this technique has been very successful in providing vibrational spectra for various interfacial systems [13][14][15][16][17][18]. Among those, the water/air interface has been the most intensively studied system, both experimentally [18][19][20][21][22][23][24][25][26] and theoretically [11,18,[25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%